L’éco-tourisme, un « modèle » de tourisme alternatif pour les territoires insulaires touristiques français ? Discussion à partir d’expériences croisées Corse-Martinique - Olivier Dehoorne; Jean-Marie Furt; Caroline Tafani (Études Caribéennes)
From a comparative study of original that puts into perspective the experiences made ​​in Corsica and Martinique islands, this paper questions the scope of eco-tourism as an alternative to mass tourism to the French islands. Both destinations are first presented briefly review the type of developed tourism and its socio-spatial causes discussed for each of the islands, there is a societal expectation pregnant for another type of tourism. It is then shown that the position of the government in terms of alternative tourism, which remains the order of discourse, encourages local actors to pursue their own projects. However, in terms of local development, the impact of these local initiatives, scattered and disjointed, are in fact very low. These observations lead to the presentation of a conceptual model for ecotourism island territories, which seeks both to clarify the definition of ecotourism is to open the discussion on recommendations for moving towards sustainability.